2019
DOI: 10.1128/aac.02611-18
|View full text |Cite
|
Sign up to set email alerts
|

A Novel 1,3-Beta- d -Glucan Inhibitor, Ibrexafungerp (Formerly SCY-078), Shows Potent Activity in the Lower pH Environment of Vulvovaginitis

Abstract: Ibrexafungerp (IBX) (formerly SCY-078) is a novel glucan synthase inhibitor whose oral availability is being evaluated for efficacy against vulvovaginal candidiasis (VVC). Bioavailability and in vitro activity are important efficacy indicators, but accepted susceptibility methods do not always accurately predict activity in an acidic environment, such as the vagina. Studies were 3-fold, as follows: (i) pharmacokinetic study following oral administration in a murine model; (ii) susceptibility testing of isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 14 publications
(16 reference statements)
0
38
0
Order By: Relevance
“…In addition, there is a novel drug called ibrexafungerp (SCY-078) that is a glucan synthase inhibitor belonging to the triterpenoid antifungal class and shows a broad in vitro and in vivo activity against a broad spectrum of Candida (Larkin et al, 2019). In vitro studies have demonstrated that this new drug has fungicidal activity against azole-resistant Candida spp.…”
Section: Cell Wall As An Antifungal Targetmentioning
confidence: 99%
“…In addition, there is a novel drug called ibrexafungerp (SCY-078) that is a glucan synthase inhibitor belonging to the triterpenoid antifungal class and shows a broad in vitro and in vivo activity against a broad spectrum of Candida (Larkin et al, 2019). In vitro studies have demonstrated that this new drug has fungicidal activity against azole-resistant Candida spp.…”
Section: Cell Wall As An Antifungal Targetmentioning
confidence: 99%
“…Ibrexafungerp was shown to have activity against biofilms from different Candida species [ 28 ]. Consistent with clinical trials in treatment of vulvovaginal candidiasis, ibrexafungerp showed potent in vitro activity in the lower pH environment of vulvovaginitis [ 39 ].…”
Section: Ibrexafungerpmentioning
confidence: 63%
“…as has been demonstrated previously [48]. Susceptibility testing was conducted with ibrexafungerp, micafungin, and fluconazole for C. albicans and C. glabrata isolates with test medium adjusted to pH values of 7.0, 5.7, and 4.5 [40]. The MIC 90 values for ibrexafungerp at pH 4.5 were dramatically lower than at pH 7.0 and 5.7.…”
Section: Pharmacologymentioning
confidence: 64%
“…In particular, with ibrexafungerp, vaginal tissue concentrations exceed plasma concentration and are higher than other antifungals, with a 9-fold higher concentration than what is seen with fluconazole [38][39][40][41]. Ibrexafungerp is extensively metabolized in the liver by cytochrome P450 3A4 isoenzymes, and <2% of a dose was recovered in urine [40].…”
Section: Pharmacologymentioning
confidence: 98%